Quarantine and anti-epidemic measures as an element of Emergency Law in Ukraine (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The concept of Emergency Law in Ukraine, its development and role in modern society are considered. The article analyses the legislative and regulatory acts governing the State of Emergency and actions in the context of emergency situations, such as natural disasters, military conflict, pandemics, etc. The key aspects of Emergency Law, such as the powers of state bodies, rights and obligations of citizens during emergency events, are considered. The article also analyses the impact of emergency law on human rights, democracy and the rule of law in Ukraine. It is stated that emergency law is a branch of law which is formed from certain elements of emergency legal regimes and affects the rights and obligations of citizens during emergencies. It covers such areas as Martial Law, State of Emergency, Emergency Situation and State of Emergency Epidemic Threat.It is specified that Emergency Law is temporary in nature and is applied only in cases of threat to national security, public order and health of the nation. It has been concluded that the main areas of improvement and development of quarantine and anti-epidemic measures in the Emergency Law system should include: improvement of legal regulation; enhancement of coordination and cooperation between public authorities; ensuring respect for citizens' rights; and consideration of the role of technology and innovation in dealing with crisis situations. The development and improvement of quarantine and anti-epidemic measures in the system of Emergency Law is crucial for ensuring the security and resilience of society. Sustained changes in global threats, such as pandemics, require constant analysis, updating and improvement of the legal response mechanism. Effective coordination, proper regulation and protection of citizens' rights are at the forefront of disaster management policy.
Keywords: quarantine measures; anti-epidemic measures; Emergency Law in Ukraine; activities of state bodies in emergency legal regimes.